2020
DOI: 10.12944/crnfsj.8.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Stevia as a Sugar Substitute and its Determinants among Health Educated Individuals and its Determinants

Abstract: Introduction: Stevia is a safe, zero calorie, low glycaemic, natural sweetener and is suitable for pre-diabetic and diabetic patients. This study investigated the perceived effect of a stevia product on taste, satiety, appetite and carbohydrate craving, and its acceptance as a sugar substitute. Methodology: An exploratory study was conducted among the randomly selected group of 73 medical students and eight lecturers. The participants consumed commercially available stevia,replacing sugar, with their morning d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The factor of health concern showed that it encouraged consumers to be aware of C. latifolia as a sugar substitute because consumers are concerned with their health. This finding is consistent with Mu'izzuddin et al (2020) where consumers were willing to continue using stevia due to its health benefits. Most respondents wanted to recommend it for diabetic patients.…”
Section: Factor Analysissupporting
confidence: 88%
“…The factor of health concern showed that it encouraged consumers to be aware of C. latifolia as a sugar substitute because consumers are concerned with their health. This finding is consistent with Mu'izzuddin et al (2020) where consumers were willing to continue using stevia due to its health benefits. Most respondents wanted to recommend it for diabetic patients.…”
Section: Factor Analysissupporting
confidence: 88%
“…As is the case in many developing countries, Malaysia has a large proportion of its population who are either suffering from diabetes or are at risk of being diabetic, and would benefit from a safe, economical, and ecologically safe alternative sweetener. 16 LEDs with narrow bandwidth, allow for the optimization of light quality and quantity and can be used efficiently in a controlled growth environment. Driven by the increase in usage and popularity of LEDs in general lighting and automotive applications, the overall production costs and system efficiencies of LEDs have improved significantly.…”
Section: Discussionmentioning
confidence: 99%
“…14 Purified stevia extract has been approved for use as a food additive and sweetener by the US Food and Drug Administration (FDA), Foods Standards Australia New Zealand (FSANZ), and by the European Food Safety Authority (EFSA). [15][16][17] The recognition by the FDA, EFSA and FSANZ has opened up the use of stevia extracts in major markets, driving global demand which is expected to grow from USD338 million in 2014 to USD554 million by the end of 2024. 15 In developed and developing countries in Asia, such as Malaysia, dried stevia leaves and leaf extracts have been popularized not only as a natural low-calorie sweetener but also as an herbal supplement, based on reported anti-inflammatory, anti-hypertensive, and anti-hyperglycaemic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The steviol glycoside (SG) compounds found in its leaves, stems and flowers form the basis of zero calorie sweeteners that have become highly popular globally due to the lack of harmful side effects commonly associated with alternative synthetic artificial sweeteners [15,16]. Purified Stevia extracts have been approved for use as a food additive and sweetener by the USA Food and Drug Administration (FDA), Foods Standards Australia New Zealand (FSANZ) and the European Food Safety Authority (EFSA) [17,18]. This recognition has seen an increase in global demand for Stevia extracts, rising from 5100 tonnes valued at USD 338 million in 2014 to an estimated 8100 tonnes with a global market value of USD 554 million by the end of 2024 [19].…”
Section: Introductionmentioning
confidence: 99%